PERPUTARAN MODAL KERJA DAN PENGARUHNYA TERHADAP PROFITABILITAS - Paul Sudjiman (Fakultas Ekonomi Universitas Advent Indonesia, 2020)
Profitability is the company's ability to obtain profits or profits. Several factors can affect profitability in the company one of which is net working capital. The purpose of this study was to determine the effect of working capital on profitability in Food and Beverage companies on the Indonesia Stock Exchange in the 2015-2018 period. The population in this study were 9 Food and Beverage companies. The technique used in sampling is purposive sampling, with a total sample of 36 industrial goods consumer companies. The data used in this research is secondary data. The analytical model used to solve the research problem is linear regression. Based on the results of descriptive statistical research, each variable has a pretty good result. With an average value (mean) of 9.0192 for Working Capital Turnover, and meet industry standards, which is six times, While the average value (mean) of 0.1437 for Profitability, which means less good because it does not meet industry standards, which is 0.15 or 15%. The analysis found that there was no significant effect between working capital on profitability with a t-test value of -1.674 and a significance value of 0.103> 0.05.